An experimental and kinetic modeling study of the autoignition delay times of trimethyl phosphite - Ofei Bruce, Frederick Nii; Zhu, Zhihan; He, Ruining; Wang, Xin; Gao, Yuke; Zhou, Chong Wen; Taufiq-Yap, Yun Hin; Curran, Henry; Li, Yang (Elsevier, 2026)
Organophosphorus compounds are used in fire suppression, acting in the gas phase by scavenging flame-propagating radicals (H, OH) and in the condensed phase by promoting char formation. However, most studies emphasize pentavalent species such as trimethyl phosphate (TMP), leaving the gas-phase oxidation chemistry of trivalent phosphorus compounds underexplored. This work presents the first detailed kinetic mechanism for trimethyl phosphite (TMPI), with a focus on its gas-phase reactivity. Ignition delay times (IDTs) of TMPI/air mixtures were measured behind reflected shock waves at 5–10 bar under lean conditions (φ = 0.1, 0.5). IDTs decrease from ∼1–3 ms at 1050 K to ∼0.01–0.03 ms at 1500 K, with shorter delays at higher pressure and richer mixtures. A reaction mechanism was constructed using quantum-chemically derived thermochemical and kinetic parameters. Rate coefficients were obtained from transition state theory, Rice–Ramsperger–Kassel–Marcus (RRKM) theory, and master equation simulations using the Master Equation System Solver (MESS), which incorporates hindered rotor and anharmonic treatments. The mechanism reproduces experimental IDTs across all conditions. IDT sensitivity analysis reveals that ignition is promoted by chain-branching and TMPI radical-generating reactions, and inhibited by radical-scavenging and recombination reactions. IDT flux analysis indicates that TMPI oxidation proceeds primarily via H- and CH3-abstraction, forming PO/PO2 intermediates. At 5 bar, PO2 predominantly branches toward CH3PO2, whereas at 10 bar, PO3 and HOPO pathways become more competitive. These results fill a critical gap in phosphorus combustion chemistry and provide a foundation for predicting the effectiveness of phosphite-based fire suppression.